2020
DOI: 10.1002/anie.201915992
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Activity Origin of a Copper‐based Electrocatalyst for Selective Nitrate Reduction to Ammonia

Abstract: Unveiling the active phase of catalytic materials under reaction conditions is important for the construction of efficient electrocatalysts for selective nitrate reduction to ammonia. The origin of the prominent activity enhancement for CuO (Faradaic efficiency: 95.8 %, Selectivity: 81.2 %) toward selective nitrate electroreduction to ammonia was probed. 15N isotope labeling experiments showed that ammonia originated from nitrate reduction. 1H NMR spectroscopy and colorimetric methods were performed to quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
811
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,072 publications
(918 citation statements)
references
References 49 publications
35
811
0
1
Order By: Relevance
“…[30] Twofold coordination is sterically favorable for the cleavage of the NO bond and had been employed in the first principles calculation for the mechanism of electrochemical reduction on catalysts. [30][31][32]…”
Section: Kinetic Mechanisms Of Electrochemical Nitrate Reductionmentioning
confidence: 99%
“…[30] Twofold coordination is sterically favorable for the cleavage of the NO bond and had been employed in the first principles calculation for the mechanism of electrochemical reduction on catalysts. [30][31][32]…”
Section: Kinetic Mechanisms Of Electrochemical Nitrate Reductionmentioning
confidence: 99%
“…From the perspective of environmental scientists, the most desirable solution for nitrate removal is to selectively reduce it to harmless gaseous nitrogen, but few non‐noble metal catalysts available today can convert nitrate into nitrogen with a high selectivity. In this regard, recent studies [ 13–16 ] by chemical scientists have attempted to promote the selectively electrocatalytic reduction of nitrate to ammonia, a value‐added product utilized as a precursor to fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the elaborate design and construction of efficient electrocatalysts is critical. Recently, we reported that the selectivity and Faradaic efficiency of Cu for electrocatalytic NO 3 − reduction to ammonia could be enhanced by the modification of its electronic structure [28]. Moreover, constructing Schottky junctions has been proved as an efficient strategy to modulate the electron density at the interface of the Schottky electrocatalysts [29,30].…”
Section: Introductionmentioning
confidence: 99%